Comparison of Clinical Characteristics Between Febrile and Afebrile Seizures Associated With Acute Gastroenteritis in Childhood - Wu, Yan-Zhang; Liu, Yao-Hua; Tseng, Chien-Ming; Tseng, Yung-Hao; Chen, Tai-Heng (Frontiers in Pediatrics, 2020)
Background Acute gastroenteritis (AGE) accompanied by seizures is not a rare scenario in childhood. We investigated the clinical features of children with febrile or afebrile seizures during AGE and aimed to identify the impact of fever in this situation-related seizure. Methods We retrospectively reviewed the medical charts of children admitted due to seizures associated with mild AGE between January 2008 and December 2017. These consecutive patients were divided into two groups: an ‘afebrile group’ whose diagnosis was compatible with ‘benign convulsion with mild gastroenteritis (CwG)’ and a ‘febrile group’ who had a fever within 24 hours of the onset of an AGE-related seizure. We compared the two groups' clinical and laboratory characteristics, electroencephalograms (EEG), neuroimaging, and outcomes. Results Of the children suffering from AGE and seizures, 41 were afebrile and 30 were febrile, with a mean age of 32.2±27.6 months. The gender, seizure semiology, frequency, duration of seizures, the time interval between AGE symptoms onset and first seizure, and levels of serum sodium and hepatic enzymes were significantly different between the two groups. The most frequently identified enteropathogen was rotavirus (33%), especially in the male and febrile subjects. Afebrile patients had more EEG abnormalities initially, but all returned to normal later. All cases had an uneventful outcome. Of note, seizure clusters (2 episodes) occurred more frequently in the afebrile patients who had a duration of AGE symptoms lasting two days or more, or white blood cell counts ≧10000/μL (p values: 0.05 and 0.04, respectively). In comparison with seven similar studies, all showed more seizure clusters, partial seizures, and a shorter interval between AGE onset and seizures in afebrile patients than in febrile patients. Contrarily, afebrile patients had longer seizure duration and lower serum hepatic transaminases than febrile patients. Conclusion Although fever partially influenced the clinical features of AGE-related seizures, febrile CwG might have pathophysiology distinctly different from that of febrile seizures. Comprehensive knowledge in discerning febrile and afebrile CwG can help to avoid unnecessary diagnostics tests, and anticonvulsants use.